Pharmaco-fMRI in Patients With Traumatic Brain Injury: A Randomized Controlled Trial With the Monoaminergic Stabilizer (–)-OSU6162. Issue 3 (May 2019) - Berginström, Nils; Nordström, Peter; Ekman, Urban; Eriksson, Johan; Nyberg, Lars; Nordström, Anna
Abstract : Objective: To examine the effects of monoaminergic stabilizer (–)-OSU6162 on brain activity, as measured by blood-oxygen-level-dependent (BOLD) functional magnetic resonance imaging (fMRI), in patients in the chronic phase of traumatic brain injury suffering from fatigue. Setting: Neurorehabilitation clinic. Participants: Patients with traumatic brain injury received either placebo ( n = 24) or active treatment ( n = 28). Healthy controls ( n = 27) went through fMRI examination at one point and were used in sensitivity analysis on normalization of BOLD response. Design: Randomized, double-blinded, placebo-controlled design. Main Measures: Effects on BOLD signal changes from before to after treatment during performance of a fatiguing attention task. Results: The fMRI results revealed treatment effects within the right occipitotemporal cortex and the right orbitofrontal cortex. In these regions, the BOLD response was normalized relative to healthy controls at the postintervention fMRI session. No effects were seen in regions in which we previously observed activity differences between patients and healthy controls while performing this fMRI task, such as the striatum. Conclusion: (–)-OSU6162 treatment had influences on functional brain activity, although the normalized regional BOLD response was observed in regions that were not a priori hypothesized to be sensitive to this particular treatment, and was not accompanied by any effects on in-scanner test performance or on fatigue. Abstract : Supplemental Digital Content is Available in the Text.